Determinants of peer-to-peer lending expansion: The roles of financial development and financial literacy - Eun Young Oh; Peter Rosenkranz (Asian Development Bank (ADB), 2020)
To explore the determinants of peer-to-peer (P2P) lending expansion, this study examines factors that impact P2P lending using a sample of 62 economies over the period 2015-2017. We investigate the effects of financial development and financial literacy on the expansion of P2P lending. The level of development of financial institutions is assessed by access, efficiency, and depth. We find that financial institutions' efficiency, financial literacy, and lower branch and ATM penetration are positively related with the expansion of P2P lending. This finding suggests that P2P lending can fill funding gaps in economies where traditional financial institutions may be less available, and thus promote financial inclusion. We also find that better information technology infrastructure and high new business density are positively associated with the expansion of P2P lending, suggesting that physical infrastructure is an essential prerequisite for it, while this is more likely to happen in dynamic business environments.
Keywords: E51; G23; G53; N20; O33; 330; financial development; financial literacy; fintech; peer-to-peer lending